Potensi Cadangan Karbon Hutan Nabundong KPH Wilayah VI Sumatera Utara - Yustika Fadilah Siregar; Basuki Wasis; Iwan Hilwan (Jurnal Ilmu Pertanian Indonesia, 2018)
Tropical forest plays a major role in global carbon (C) cycle, about 50% of the total carbon is stored in biomass and 50% is stored in the top 1 m of the soil. Research on the potential for carbon stock was conducted in Nabundong forest in Padang Lawas Utara District. It was managed by the FMU (Forest Management Unit) region VI North Sumatra. This research aims to identify forest structure, estimate above ground biomass using allometric equations, and determine the carbon stock potential of Nabundong forest. The results showed that stratum I (212.68 tonC/ha) had higher carbon stock than stratum II (151.78 tonC/ha).